Peningkatan Minat Belajar Siswa Kelas V Sd Negeri Gajahmungkur 03 Semarang Terhadap Pembelajaran Pendidikan Pancasila Dengan Menggunakan Media Educandy dan Wordwall - Yunita Fitri Yaningsih; Afrenna Tri Nurrahmasari; Luthfiana Nur Lathifah; Nur Indah Wahyuni (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The researchers conducted research on EduCandy and Wordwall with the aim of improving student learning outcomes and students' understanding of the material on the application of values and norms in everyday life. This research was conducted by researchers at SD Negeri Gajahmungkur 03 Semarang, where the population chosen was all students at SD Negeri Gajahmungkur 03 Semarang, while the samples taken were students of class V at SD Negeri Gajahmungkur 03 Semarang. The method used by researchers to write articles uses the qualitative description method. This method consists of interviews with class teachers and school principals with the aim of finding out the initial conditions of the classes that will be used as samples. The next activity is observation to find out more about the characteristics of students and selecting appropriate media for the research process regarding the application of values and norms in everyday life where researchers use EduCandy and Wordwall media. From the research results, it was found that all students achieved increased grades and understanding of the material using interesting and interactive media, namely EduCandy and Wordwall. Based on these results, it can be concluded that the use of interesting media such as EduCandy and Wordwall can improve student learning outcomes regarding the application of values and norms in everyday life, make students more enthusiastic and happy to learn, and can create learning conditions that are more interactive and meaningful than usually.